2001
DOI: 10.1021/jp010172y
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Scanning Tunneling Microscopy of Underpotential Deposition of Copper at Pt(100) Electrodes Coated with an Iodine Monolayer

Abstract: Reported here are in situ scanning tunneling microscopy (STM) results of underpotential deposition (UPD) of copper at an iodine-modified Pt(100) electrode. The cyclic voltammograms reveal that an iodine adlayer strongly adsorbed on Pt(100) resulted in a 350 mV delay of Cu deposition with respect to that of a bare Pt(100) electrode. High-quality in situ STM imaging reveals the atomic structures of the iodine adlayers before and after the deposition of Cu adatoms. Depending on the dosage of iodine vapor to an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The Pt(1 1 1) electrode was immersed from the quenching tube with a thin film of water on top, which protected this Pt electrode from adsorption of contaminants in the ambient. The STM cell was equipped with a Pt counter and a Pt quasi-reference electrodes [27][28][29]. All potentials reported here are converted into a scale of a Ag/AgCl electrode.…”
Section: Methodsmentioning
confidence: 99%
“…The Pt(1 1 1) electrode was immersed from the quenching tube with a thin film of water on top, which protected this Pt electrode from adsorption of contaminants in the ambient. The STM cell was equipped with a Pt counter and a Pt quasi-reference electrodes [27][28][29]. All potentials reported here are converted into a scale of a Ag/AgCl electrode.…”
Section: Methodsmentioning
confidence: 99%
“…The Pt(111) electrodes used for STM and voltammetric experiments were made from a polycrystalline Pt wire. , The obtained Pt(111) bead electrode was fist annealed with a hydrogen torch, followed by quenching in hydrogen-saturated Millipore water. Pt wires were used as the counter and quasi-reference electrodes in the STM environment. All potentials reported here are converted into the scale of a Ag/AgCl electrode. Prior to the deposition of a Cu film, the potential of Pt(111) was scanned negatively at 50 mV/s to −0.3 V (onset of hydrogen evolution) from the open-circuit potential (OCP) of ∼0.7 V. This potential sweeping removed the thermal oxide produced in the annealing-and-quenching pretreatment.…”
Section: Methodsmentioning
confidence: 99%
“…The solution-based electrodeposition of metals has been extensively studied academically as well as provided industrial solutions for practical devices. , One interesting and applicable avenue of research has been the use of surface modifiers to affect the structure and morphology of deposited metals, for example, surfactants, organic molecules, and halide salts . In liquid-based electrochemical deposition, iodine adsorption on metal surfaces is well known to influence the kinetics of crystallization and the morphology of metal growth and has been frequently utilized to form compact, uniform films. For solid-state electrodeposition, several research teams have shown that modification of the lithium-metal surface has significantly improved the galvanic cycling properties using solid-state electrolytes; however, iodine adsorption has not been evident during the solid-state deposition of lithium metal nor has its influence on cell failure. Understanding the electrochemical interphase is a vital step to engineering practical SSBs.…”
Section: Introductionmentioning
confidence: 99%